Isolation and Identification of Biosurfactant Producing Bacteria from Tofu Liquid Waste UD. Dika Putra, Riau Province - Sonia Kamallia; M. Hasbi; Budijono Budijono (Universitas Riau, 2021)
Tofu liquid waste contains high levels of organic matter, especially protein and amino acids. These organic compounds can be proteins, carbohydrates and fats. Most of the bacteria are able to use oil or fat as a source of carbon and energy, bacteria that have this ability are often known as lipolytic bacteria. This study aims to obtain biosurfactant producing bacteria from tofu wastewater. This research was conducted from July - September 2020. The method used in this research is survey method and emulsification method. The media used for bacterial isolation were Tryptic Soy Broth (TSB) and Tryptic Soy Agar (TSA). 6 of the isolates are able to produce biosurfactants. Morphological and biochemical characteristics indicate six bacterial genera, namely Genus Agrobacterium, Proteus, Proteus, Citrobacter, Enterobacter, and Serratia. The bacteria obtained are bacteria that have the potential to degrade oil in a polluted environment.